Perception and Challenge for Integrating ICT in English Language Teaching - Julmukya, Tiarsa; Sujarwati, Iis (Beyond Words, 2024)
AbstractThe field of education has seen asignificantchange due to information and communication technology (ICT).Education ministries worldwide have already approved the integration of ICT into educational systems. Since a decade ago, English Language Teaching (ELT) has been integrated with information and communication technology (ICT) in secondary schools.Adoption of and efforts for integrationICT in ELT differ significantly from the state ofanactual implementation. The study seeks to investigate the attitudes of English teachers at the secondary level regarding ICT integration in Communicative Language Teaching (CLT) as well as the variables that prevent its implementation. The article also makes an effort to look at the difficulties English instructors in secondary schools have in successfully integrating ICT into their classrooms. In an effort to assess instructors' attitudes on using ICT in ELT. The result shows teachers' attitudes towards ICT-integratedCLT 79.62%,which obtainedthehigh category,andanother aspect was75.91%,whichgotthehighsortinfacing challenges due totheimplementationof ICT. Overall,77% of teachers achievedgood scores in all aspects.